PFA-100 System: A New Method for Assessment of Platelet Dysfunction - Mammen, Eberhard F.; Comp, Philip C.; Gosselin, Robert; Greenberg, Charles; Hoots, W. Keith; Kessler, Craig M.; Larkin, Edward C.; Liles, Darla; Nugent, Diane J. (Seminars in Thrombosis and Hemostasis, 2023)
This is a celebratory reprint of a historical paper published in STH in 1998. The original Abstract follows.The PFA-100 system is a platelet function analyzer designed to measure platelet-related primary hemostasis. The instrument uses two disposable cartridges: a collagen/epinephrine (CEPI) and a collagen/ADP (CADP) cartridge. Previous experience has shown that CEPI cartridges detect qualitative platelet defects, including acetylsalicylic acid (ASA)-induced abnormalities, while CADP cartridges detect only thrombocytopathies and not ASA use. In this seven-center trial, 206 healthy subjects and 176 persons with various platelet-related defects, including 127 ASA users, were studied. The platelet function status was determined by a platelet function test panel. Comparisons were made as to how well the defects were identified by the PFA-100 system and by platelet aggregometry. The reference intervals for both cartridges, testing the 206 healthy subjects, were similar to values described in smaller studies in the literature (mean closure time [CT] of 132 seconds for CEPI and 93 seconds for CADP). The use of different lot numbers of cartridges or duplicate versus singleton testing revealed no differences. Compared with the platelet function status, the PFA-100 system had a clinical sensitivity of 94.9% and a specificity of 88.8%. For aggregometry, a sensitivity of 94.3% and a specificity of 88.3% were obtained. These values are based on all 382 specimens. A separate analysis of sensitivity by type of platelet defect, ASA use versus congenital thrombocytopathies, revealed for the PFA-100 system a 94.5% sensitivity in identifying ASA users and a 95.9% sensitivity in identifying the other defects. For aggregometry, the values were 100% for ASA users and 79.6% for congenital defects. Analysis of concordance between the PFA-100 system and aggregometry revealed no difference in clinical sensitivity and specificity between the systems (p > 0.9999). The overall agreement was 87.5%, with a Kappa index of 0.751. The two tests are thus equivalent in their ability to identify normal and abnormal platelet defects. Testing 126 subjects who took 325 mg ASA revealed that the PFA-100 system (CEPI) was able to detect 71.7% of ASA-induced defects with a positive predictive value of 97.8%. The overall clinical accuracy of the system, calculated from the area under the receiver operating characteristic curve, was 0.977. The data suggest that the PFA-100 system is highly accurate in discriminating normal from abnormal platelet function. The ease of operation of the instrument makes it a useful tool to use in screening patients for platelet-related hemostasis defects.
Keywords: PFA-100 system; thrombocytopathies; von Willebrand disease; aspirin; platelet aggregometry; bleeding time